Distribution of the common nettle Urtica dioica L. and annual nettle U. urens L. in the Russian Federation - N. N. Luneva; T. Yu. Zakota; Y. A. Fedorova (Труды по прикладной ботанике, генетике и селекции)
Two widespread weedy species of Urtica L. (Urticaceaea Juss.), common nettle (Urtica dioica L.) and annual nettle (U. urens L.), possess many useful properties, so any information on their distribution is of practical interest. Numerous scientific publications with open access were used to map the areas of distribution for these species in the Russian Federation. While mapping the spatial arrangement of these taxa, the data on the frequency of their occurrence in separate administrative subdivisions of the country were employed. Areas where occurrences of an individual nettle species are scored as “very often”, “often”, “usually” or “often” were blended into one territory characterized with the “often” occurrence: this is the optimum zone for the species in question. Similarly, the pessimum zone for the species was identified as a combined territory of the areas where the occurrence was marked as “very rarely”, “rarely”, “infrequently” or “sporadically”. The pessimum zone included the areas located in the north of the range of species distribution: they are characterized by cooler and more humid environmental conditions than the optimum zone. The pessimum also incorporated the lands stretching in the southern part of the range: their environmental conditions are drier and warmer than those in both the optimum zone and the northern part of the pessimum zone. Therefore, plants of the same species, occurring in different parts of their area of distribution, are adapted to different hydrothermal conditions, which should be taken into account when selecting forms for further possible cultivation and use.